A comparative analysis of forest area differences between statistics information and spatial thematic maps. Issue 2 (3rd April 2022) - Park, Jeong Mook; Lee, Yong Kyu; Lee, Jung Soo
Abstract: Securing reliable data on forest areas is necessary for the establishment of various policies and decision-making for forest administration. In this study, the definition of forest, minimum partitioning criteria, purpose of production, production method, and period of update were analyzed, which were prescribed for the statistics (Forest Basic Statistics [FBS] and Cadastral Statistical Annual Report [CSAR]) and spatial data (digital forest type map, sub-divided land cover map, continuous cadastral map). Forested area was calculated according to the statistics and spatial data for Wonju, Gangwon-do, and the forest area between statistics and spatial data was quantitatively compared. In terms of the definition of forest and minimum partitioning criteria, the FBS and digital forest type maps were similar, and the land cover map, CSAR, and continuous cadastral maps were different in these aspects. About forest area, there was a difference in each forestry data. The highest was CSAR(61, 406 ha) and the lowest was Sub-divided Land Cover Map(57, 818 ha). This is thought to be because there were some types of spatial areas that were classified as forest in the digital forest type map but classified as cropland, grassland, settlement, and bare land in the sub-divided land cover map and continuous cadastral map. Moreover, in the case of the continuous cadastral map, it is thought that there was an error in the area calculation due to differences between the land category in the map and the actual land use status, which led to differences in the calculated area between different types of spatial data. For future statistics and spatial data, appropriate measures should be established to address the issue of the differences between the calculated area due to misclassification during visual reading, and the difference between the land category in the map and the actual land use status. The calculated forest area should be used for research on the definition of forest, the purposes of map production, and production methods for each type of information and data